Perancangan Interior Street Food Center di Tulungagung - Natasya Christy; Stephanus P Honggowidjaja (Intra, 2016)
Interior Design Street Food Center aims to accommodate the social needs of Tulungagung citizens with designing a comfortable place to eat and interesting place to gather with friends , family , and colleagues . In addition , the design has a target to provide new tourist attractions to residents of Tulungagung and also gives an interesting design innovations in town. This design represents a concept of street food with an interior street scenes accompanied by an indoor garden atmosphere that takes the concept of alun - alun Tulungagung, and the atmosphere of the beach which a tourism icon of the Tulungagung. These three concepts are combined together in a interior design so that food center it has a good atmosphere and cozy.